The Role of the University’s Strategic Entrepreneurship in the Relationship between Social Responsibility and Investment in Human Capital: A Field Study on Government Services Sector in Al-Jouf Region - Mohammed, Sanaa (The Arab Journal of Administration, 2023)
Purpose: This study aims to identify the role of university’s strategic entrepreneurship play in the relationship between the dimensions of social responsibility (economic responsibility, legal responsibility, ethical responsibility, philanthropic responsibility) and investment in human capital. Methodology and method: The research used the descriptive and analytical approach, in addition to the field study as a method for research, and the research was applied to a sample (400) individuals and were determined according to the size of the study population (2091) individuals, and SPSS version (25) was used in data analysis, and the AMOS version (25) To conduct the necessary statistical analyzes. Results and recommendations: There is an indirect and significant impact of the dimensions of social responsibility (economic responsibility, human responsibility, responsibility for caring for human resources, and responsibility towards protecting the environment and natural resources) on investment in human capital through the variable of the interfering medium (strategic entrepreneurship). Accordingly, we recommend the good selection of leaders and training programs in order to raise the level of strategic leadership of the university.